Food security and sovereignty in Providence Rhode Island local food system - Anne Palliser (Urban Food Systems Symposium, 2020)
The urban, local food system in Providence Rhode Island has a network of urban gardens and farms throughout the city where food is grown for families and to sell at the many farmers markets. It also has a large food hub selling local food to restaurants, schools, hospitals and universities in the city and further afield. The Providence food system aims to develop the local economy through provision of local, sustainably produced food and to reduce food insecurity for the poorest communities in the city. However, it has been argued that while such systems remain embedded in a market-driven approach to development, significantly addressing food insecurity is problematic (Alkon et al., 2012; Edelman, 2014; Prost et al., 2018). How the Providence local food system addresses food security, both in terms of increasing food resilience against future climate related shocks and currently, for the poorest communities in the city, is discussed in this paper, which also engages with some of the problems faced by local farmers. This research is based on 21 interviews, comprising 32 people from all levels of Providence local food system. It was undertaken over four months in late 2019 through a New Zealand Fulbright Scholarship.
Keywords: food sovereignty; food system reform